Four new species of the genus Lepidostoma Rambur (Trichoptera: Lepidostomatidae) from the Indian Himalayas, with a checklist to its Indian species - Saini, Malkiat S.; Parey, Sajad H. (Zootaxa, 2011)
Four new species of the genus Lepidostoma Rambur are described and illustrated from the Indian Himalayas, namely Lepidostoma kashmiricum sp. nov. from Pahalgam (Jammu & Kashmir), Lepidostoma himachalicum sp. nov. from Raskar (Himachal Pradesh), Lepidostoma dirangense sp. nov. from Dirang (Arunachal Pradesh) and Lepidostoma meghalayaense sp. nov. from Cherrapunge (Meghalaya), all in the Lepidostoma ferox Branch. With this addition of 4 new species, the genus Lepidostoma is now represented by 35 species from India. A checklist to all species of genus Lepidostma of India is included.